Effect of Water Treatment and Immersion in Calcium Salt Solutions on the Quality of Fruits of Peumo Pink Tomato ( Solanum lycopersicum L.) Stored under Cold Conditions - Julio Correa; Asuncion Amoros; Herman Patricio Silva; José Ignacio Covarrubias; Victor Hugo Escalona (Polish Journal of Food and Nutrition Sciences)
Tomato is one of the most consumed vegetable crops worldwide. In the break stage, it is perishable, and it has a postharvest life that does not exceed three weeks at 12 to 15°C. The aim of this study was to evaluate the effect of immersion in water and in calcium salt solutions on the metabolism and quality of tomato of traditional Peumo Pink cultivar stored for 28 days at 10ºC plus a simulated trading period of 2 days at 20ºC. Fruits were treated in water at 5, 45 and 60ºC at two immersion times of 1 and 4 min or in 2% solutions of calcium chloride, lactate and propionate at 10 and 45ºC for 4 min. The respiration rate, ethylene production and heat shock protein gene expression as well as firmness, total phenolic content and antioxidant capacity of tomato were determined. Dipping in water at 60°C reduced the loss of firmness and respiratory rate of tomatoes up to 21 days at 10°C + 2 days at 20°C. Treatment in water at 45°C for 4 min and at 60°C for 1 or 4 min stimulated heat shock protein gene expression. However, fruit treated at 60°C for 1 or 4 min showed uneven ripening; hence, the immersion in water at 45°C for 4 min was the most recommended to extend the postharvest life of tomatoes. In turn, the immersion in calcium lactate and propionate solutions at 45°C increased total calcium content and maintained firmness after 28 days at 10°C + 2 days at 20°C. The use of high temperature and calcium salts for dipping would be beneficial to provide the vegetal tissues with calcium and reduce the softening of the tomato after prolonged cold storage.